Handwriting criteria analysis of lower primary school children / Norzehan Sakamat and Noor Elaiza Abd Khalid - Sakamat, Norzehan; Abd Khalid, Noor Elaiza (2019)
First ‘screening’ of detecting children with handwriting difficulty is usually done by the school teachers. The evaluation is called global legibility assessment of handwriting which involve a process of assessment based on checklist scores given to the handwriting product. However the global legibility assessment is to suffer from limited accuracy, sensitivity, and reliability. The paper aims is to seek the association of the result produces by global legibility assessment done by teachers and findings made by previous researchers who uses other types of evaluation tools including computerized evaluation tools. One hundred and forty students at the age between six year old to eight years old and six homeroom teachers were involved in this study which takes place at an international school in Putra Height, Selangor, Malaysia. The testing procedure is adapted from Minnesota Handwriting Assessment(MHA) tools where students are required to finish up three near-copying task of a preset sentences. They were given two and half minutes to finish up each task. After the handwritten samples were obtained, the teachers are required to evaluate the students’ handwriting based on the given questionnaire. The analysis focus on three aspect: readability, acceptable size and shape of the handwritten product(RASS); size consistency and completion time. Results found that the three handwriting characteristics that were evaluated improved with age and maturity of the children. These results prove that the global legibility assessment done by the teachers are consistent with the previous findings by various researchers. Global methods of assessing are proven to be a reliable source of first stage screening of children with handwriting difficulty.